Especie nueva de Inga (Leguminosae: Mimosoideae) de la Sierra Madre Oriental, México - Sousa S., Mario (Instituto de Ecología, A.C., 1995)
A new species of Inga is described, I. huastecana from the Sierra Madre Oriental, in the Mexican states of Queretaro, Veracruz and Puebla. It appears to be related to I. hayesii Benth. and also, but in lesser degree, with I. pinetorum Pittier.